Sosialisasi Program Kreativitas Mahasiswa (PKM) dan Pelatihan Pembuatan Proposal PKM Bagi Mahasiswa - Ito Setiawan; Retno Waluyo; Banu Dwi Putranto; Farah Mei Maulida; Hani Bela Pratini (Universitas Pahlawan Tuanku Tambusai, 2023)
PKM is a manifestation of the implementation of the Tridharma of Higher Education which was launched by the Directorate General of Higher Education under the management of Belmawa, which is one of the efforts to grow, accommodate and realize students' creative and innovative ideas. The division in charge of PKM at Amikom University in Purwokerto is the Student and Alumni Affairs section. Student Affairs and Alumni are targeting a total of 200 proposals for internal selection. With these many targets, there is a need for socialization carried out by the Student and Alumni section regarding the PKM 2023 program. From these problems, one solution is to conduct training on making PKM proposals for students. The purpose of the PKM socialization and training is to assist students in making PKM proposals in accordance with existing guidelines. The methods used in socialization and training are the preparation stage, the implementation stage and the evaluation stage. The results of the training are that students can make PKM proposals in accordance with the Guidelines and can fill in data up to uploading the proposal in SIMBELMAWA.